A baseline tool for predicting response to peginterferon alfa‐2a in HBeAg‐positive patients with chronic hepatitis B. Issue 5 (29th June 2018) - Chan, H. L. Y.; Messinger, D.; Papatheodoridis, G. V.; Cornberg, M.; Xie, Q.; Piratvisuth, T.; Ren, H.; Kennedy, P. T.; Thompson, A.; Caputo, A.; Bakalos, G.; Pavlovic, V.; et al.
Summary: Background: Peginterferon induces off‐treatment responses in approximately one‐third of patients with hepatitis B e antigen (HBeAg)‐positive chronic hepatitis B. Aim: To develop an easy‐to‐use baseline prediction score to identify hepatitis B virus (HBV) genotype B‐/C‐infected HBeAg‐positive Asian patients likely to respond to peginterferon alfa‐2a. Methods: Generalised additive models, multiple logistic regression (MLR) analysis and internal validation methods were applied to data from 647 HBeAg‐positive patients from China, Hong Kong and Taiwan to develop a scoring system to predict response 24 weeks after completing a 48‐week course of peginterferon alfa‐2a. Results: Five baseline factors (age, sex, alanine aminotransferase ratio, hepatitis B surface antigen (HBsAg) level and HBV DNA level) were retained in the final MLR for HBeAg seroconversion and used to develop a scoring system from 0 to 7. Among patients with scores of 0‐1, 2‐3, 4 or ≥5, HBeAg seroconversion was achieved in 6.4% (6/94), 23.0% (61/265), 36.4% (67/184) and 54.8% (57/104), respectively, and a combined response (HBeAg seroconversion plus HBV DNA <2000 IU/mL) in 5.3% (5/94), 12.8% (34/265), 25.0% (46/184) and 36.5% (38/104), respectively. Among patients with scores of 0‐1, 2‐3, 4 or ≥5, 57.0% (53/93), 12.3% (31/253), 3.4% (6/178) and 1.0% (1/100) had HBsAg ≥20 000 IU/mL at treatment Week 12; only 3/91 (3.3%) with HBsAg ≥20 000 IU/mL experienced a combined response at 24 weeks post‐treatment (negative predictive value = 97% [88/91]). Conclusion: A pre‐treatment scoring system using readily available baseline characteristics identifies HBeAg‐positive Asian patients likely to experience sustained HBeAg seroconversion after treatment with peginterferon alfa‐2a.